Molecular Diagnosis of Major Emerging Tomato Infecting Viruses and Their Vector Population Dynamics (Journal of Science and Technology Research, 2024)
Tomato is an important vegetable crop in Bangladesh, growing year-round in both kitchen gardens and large-scale commercial farming. Many diseases affect the solanaceous vegetable crop, particularly viral diseases. Using modern molecular methods and vector population dynamics, we attempted to detect major emerging viral infections of tomato. A survey was conducted in different locations of Bangladesh, namely Rajshahi, Jamalpur, Jessore, and Joydebpur to assess viral infections in tomato and associated insect vectors. Various forms of viral disease symptoms were observed to infect tomato in the examined area, including mosaic, yellowing, mottling, leaf curling, and bud necrosis, with a incidence ranging from 20 to 100%. Among the different viral diseases, leaf curl was the most common, accounting for 100% of the cases. Field resistance to viral infections was investigated among the BARI released tomato varieties, and all of the tomato types tested were infected with the leaf curl virus. In addition, the examined area had a moderate to high prevalence of chlorosis and purple vein disease. The viruses identified by DACELISA, PCR, and RT-PCR were tomato leaf curl virus (ToLCV) and groundnut bud necrosis virus (GBNV).J. of Sci. and Tech. Res. 6(1): 161-167, 2024